Protein–cofactor binding and ultrafast electron transfer in riboflavin binding protein under the spatial confinement of nanoscopic reverse micelles. Issue 2 (7th January 2013) - Saha, Ranajay; Rakshit, Surajit; Verma, Pramod Kumar; Mitra, Rajib Kumar; Pal, Samir Kumar
<x xml:space="preserve">Abstract</x> In this contribution, we study the effect of confinement on the ultrafast electron transfer (ET) dynamics of riboflavin binding protein (RBP) to the bound cofactor riboflavin (Rf, vitamin B2), an important metabolic process, in anionic sodium bis(2‐ethylhexyl) sulfosuccinate reverse micelles (AOT‐RMs) of various hydration levels. Notably, in addition to excluded volume effect, various nonspecific interactions like ionic charge of the confining surface can influence the biochemical reactions in the confined environment of the cell. To this end, we have also studied the ET dynamics of RBP–Rf complex under the confinement of a cationic hexadecyltrimethylammonium bromide (CTAB) RMs with similar water pool size to the anionic AOT‐RMs towards simulating equal restricted volume effect. It has been found that the spatial confinement of RBP in the AOT‐RM of w0 = 10 leads to the loss of its tertiary structure and hence vitamin binding capacity. Although, RBP regains its binding capacity and tertiary structure in AOT‐RMs of w0 ≥20 due to its complete hydration, the ultrafast ET from RBP to Rf merely occurs in such systems. However, to our surprise, the ET process is found to occur in cationic CTAB‐RMs of similar volume restriction. It is found that under the spatial confinement of anionic AOT‐RM, the isoalloxazine ring of Rf is improperly placed in the protein nanospace so that ET between RBP and Rf is not permitted. This anomaly in the binding behaviour of Rf to RBP in AOT‐RMs is believed to be the influence of repulsive potential of the anionic AOT‐RM surface to the protein. Our finding thus suggests that under similar size restriction, both the hydration and surface charge of the confining volume could have major implication in the intraprotein ET dynamics in real cellular environments. Copyright © 2013 John Wiley & Sons, Ltd.